2021
DOI: 10.1080/21681376.2020.1860807
|View full text |Cite
|
Sign up to set email alerts
|

New geography in old territories: a multivariate approach based on Portuguese regions

Abstract: This paper studies the strongly asymmetrical distribution of the population, quality of life and economic development in Portugal. It identifies homogeneous areas supported by an analysis of competitiveness, cohesion and environmental quality dimensions. Drawing on a multivariate approach, its findings reveal differences in terms of development across the country. The study identified groups of regions with common characteristics that go beyond the standard north-south or coastal-inland distinctions. Metropoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
2
5
0
1
Order By: Relevance
“…Larrán et al (2019) focus on the extent of information reported in universities’ sustainability reports and suggest that sustainable practices can logically differ among universities in different regions. There are territorial asymmetries in Portugal in population distribution and economic development because the coastal regions are more characterized by youth, urbanism and economic exchanges compared to the more unpopulated inland (Rego et al , 2021)…”
Section: Methodsmentioning
confidence: 99%
“…Larrán et al (2019) focus on the extent of information reported in universities’ sustainability reports and suggest that sustainable practices can logically differ among universities in different regions. There are territorial asymmetries in Portugal in population distribution and economic development because the coastal regions are more characterized by youth, urbanism and economic exchanges compared to the more unpopulated inland (Rego et al , 2021)…”
Section: Methodsmentioning
confidence: 99%
“…As for works done on Portuguese territory and in addition to the aforementioned work by Rego et. al (2021), the following works should be mentioned: Dionísio and Rego (2020), Amado et.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Many other authors also resorted to multivariable statistics, such as Rego et. al (2021) who studied the strongly asymmetrical distribution of the population, quality of life and economic development in Portugal.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Additionally, it is worth analysing the value-added transference from the sphere of urban areas of consumption to the field of production with GI, which is mainly located in low density territories. In other words, it is important to transfigure these GI products into elements of cohesion and sustainable development and factors of reduction of the strongly asymmetrical distribution of the population, improving quality of life and economic development between the coastal and the inland regions and/or the urban and rural areas [6].…”
Section: Opinionmentioning
confidence: 99%
“…However, despite measures to support its production, which is viewed as a valuable national development strategy, the small producers who underwrite it and their two associated cooperatives face several difficulties. Some struggles are related to the socioeconomic context, to the adverse impact of climate changes, to the complex and limited access to global value chains, and to the worldwide demand pressure for higher cocoa quality and productivity [6,7]. Others adversities are the market price instability which is dependent of the cocoa world market prices and the lack of premium price in the domestic market, even though cocoa is a product with organic value-adding characteristics and attributes.…”
Section: Opinionmentioning
confidence: 99%